Healthy People 2010 Oral Health Objectivesthe Role of AAPHD - Rebecca King, DDS, MPH, AAPHD (Blackwell Synergy, 2001)
AAPHD’s role in working toward the Healthy People 2010 Oral Health objectives is not a new one, and is closely related to our ongoing activities because our visions are the same-healthier people. Rather, the Healthy People 2010 oral health objectives provide tools that we can use to pursue our organizational goals. We are working to strengthen our role in this capacity. We have a diverse, geographically dispersed membership that is knowledgeable about oral health issues-no one knows these issues better than we do. As part of our diversity (members working in academic institutions; local, state, and federal health departments and agencies; and the private sector), we have the capacity to put a face on these issues- the Healthy People 2010 objectives help us put a number on them.